2021
DOI: 10.1097/cce.0000000000000387
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy for Mortality Prediction With Additive Biomarkers Including Interleukin-6 in Critically Ill Patients: A Multicenter Prospective Observational Study

Abstract: Objectives: Several inflammation markers have been reported to be associated with unfavorable clinical outcomes in critically ill patients. We aimed to elucidate whether serum interleukin-6 concentration considered with Sequential Organ Failure Assessment score can better predict mortality in critically ill patients. Design: A prospective observational study. Setting: Five university hospitals in 2016–2018. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Yamamoto et al found that IL-6 level on day 3 after admission had satisfactory discrimination ability for mortality in critically ill patients (AUC = 0.766; p < 0.001) [39]. IL-6 level showed somewhat lover discriminative ability in hospitalized patients (AUC = 0.74, p < 0.0001), according to a study by Laguna-Goya et al [40].…”
Section: Discussionmentioning
confidence: 94%
“…Yamamoto et al found that IL-6 level on day 3 after admission had satisfactory discrimination ability for mortality in critically ill patients (AUC = 0.766; p < 0.001) [39]. IL-6 level showed somewhat lover discriminative ability in hospitalized patients (AUC = 0.74, p < 0.0001), according to a study by Laguna-Goya et al [40].…”
Section: Discussionmentioning
confidence: 94%
“…2 Interleukin-6 (IL-6) is a critical cytokine involved in the innate immune response in sepsis and other severe infections and contributes in conjunction with other pathophysiological processes to adverse outcomes. [3][4][5][6] The modulation of IL-6 dynamics and its multiple different signalling pathways represents a potentially exciting therapeutic opportunity for severe infection given the key role for this cytokine and associated signalling. 3,6,7 The inflammatory role of IL-6 is mediated not by the classical or trans-presentation modes of action through a membrane bound receptor (IL6R), but through a trans-signalling mechanism where IL-6 binds a soluble form of the receptor that subsequently interacts with membrane bound signalling molecule, gp130, on cells.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] The modulation of IL-6 dynamics and its multiple different signalling pathways represents a potentially exciting therapeutic opportunity for severe infection given the key role for this cytokine and associated signalling. 3,6,7 The inflammatory role of IL-6 is mediated not by the classical or trans-presentation modes of action through a membrane bound receptor (IL6R), but through a trans-signalling mechanism where IL-6 binds a soluble form of the receptor that subsequently interacts with membrane bound signalling molecule, gp130, on cells. 7,8 Inhibition of both membrane and soluble IL6R using monoclonal antibodies such as tocilizumab or sarilumab (collectively known as IL-6 receptor antagonists, IL6RAs) have been successfully trialled in critically ill patients with COVID-19 and are now considered a standard treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Our current best treatments remain antimicrobial therapy and organ support, with no licenced treatments outside these interventions [2]. Interleukin 6 (IL-6) is a critical cytokine involved in the innate immune response in sepsis and other severe infections and contributes in conjunction with other pathophysiological processes to adverse outcomes [3][4][5][6]. The modulation of IL-6 dynamics and its multiple different signalling pathways represents a potentially exciting therapeutic opportunity for severe infection given the key role for this cytokine and associated signalling [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin 6 (IL-6) is a critical cytokine involved in the innate immune response in sepsis and other severe infections and contributes in conjunction with other pathophysiological processes to adverse outcomes [3][4][5][6]. The modulation of IL-6 dynamics and its multiple different signalling pathways represents a potentially exciting therapeutic opportunity for severe infection given the key role for this cytokine and associated signalling [3,6,7]. The inflammatory role of IL-6 is mediated not by the classical or trans-presentation modes of action through a membrane bound receptor (IL6R), but through a trans-signalling mechanism where IL-6 binds a soluble form of the receptor that subsequently interacts with membrane bound signalling molecule, gp130, on cells [7,8].…”
Section: Introductionmentioning
confidence: 99%